Hypercoagulability in Cushing's syndrome: From arterial to venous disease. Issue 2 (March 2021) - St-Jean, Matthieu; Lim, Dawn S.T.; Langlois, Fabienne
Abstract : Cushing's syndrome (CS) is associated with multisystemic complications; the hematological system is not spared. Alteration in hemostatic parameters and in vivo endothelial dysfunction lead to increased thrombotic events. Arterial and venous thrombotic events carry significant morbidity and mortality. Death from cardiovascular and pulmonary embolism account for more than 50% of mortality. Surgery is a critical period; close to 50% of events occur in the 1–2 months after intervention. The evaluation and risk stratification of patients with CS is key to prevent events, balancing the risk-benefit of anticoagulation in this population. This current review will focus on up-to-date data on epidemiology, pathophysiology and management of hypercoagulability in CS.